Pengelolaan Sampah Berbasis Masyarakat di Destinasi Wisata untuk Mewujudkan Lingkungan Sehat dan Berkelanjutan: Desa Paya Jeget Kecamatan Pegasing Kabupaten Aceh Tengah - Yusriati Yusriati; Aulia Zikra; Zulhilmi Zulhilmi; Nurhidayati Nurhidayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Waste management is a major challenge in sustainable development, particularly in areas with tourism potential. Paya Jeget Village, Pegasing District, Central Aceh Regency, a developing tourist destination, is addressing waste management issues that require serious attention. The increasing number of tourists visiting the village has the potential to significantly increase the volume of waste generated. Without proper management, this condition can threaten environmental sustainability and public health. Therefore, a community-based waste management approach is needed that involves the active participation of all stakeholders, from village government, community leaders, tourism operators, and the general public. The objectives of this community service activity are to increase public knowledge and awareness about sustainable waste management, develop an integrated community-based waste management system, and establish independent community waste management groups to realize a clean and healthy tourist destination. Implementation methods include outreach and education, practical training, the formation of working groups, and ongoing mentoring to ensure the program runs consistently. The community service activities carried out on June 2, 2025 have achieved the following results: 45 participants participated in the outreach activities, 90% of participants understood the importance of waste from a religious and environmental perspective, the formation of collective awareness to maintain environmental cleanliness, the formation of a waste management group consisting of 15 members, the availability of waste sorting places at three strategic points, the implementation of waste sorting activities at the household level, and the start of organic waste composting activities. In addition, this activity also succeeded in fostering a spirit of mutual cooperation in waste management and improving residents' skills in processing organic waste into compost.